Industrial profile of exports from the State of Rio Grande do Sul and the deindustrialization hypothesis (Research, Society and Development, 2021)
This paper aims to analyze the industrial profile of The State of Rio Grande do Sul, seeking to answer the following question: Is it occurring a process of deindustrialization in The State of Rio Grande do Sul? In this sense, were adjusted two Vector Error Correction Models (VEC), with the following dependent variables: exports of manufacturing industry (high intensity, medium-high, medium-low and low intensity) of The State of Rio Grande do Sul and exports of non-industrial products. The independent variables were real effective exchange rate; price index of non-energy commodities; and coefficient of the commercial openness degree. The results indicated that the exports of non-industrial products presented a greater increase than the products by technological intensity. In relation to the estimation of VEC, the results indicated that the exchange devaluation stimulates the exports; the commercial openness was extremely damaging to the exports and the price index of non-energy commodities variable presented opposite sign to the expected. Finally, we concluded that there are strong evidences of the deindustrialization process in The State of Rio Grande do Sul.